Exploring the Components of Management Information Systems: Software, Database, and Brainware - A Literature Review - Ramadhona, Nova; Erliyani, Ita; Rosdiana (International Transactions on Education Technology (ITEE), 2023)
A more in-depth information system is often referred to as a sub-system, which is a more specific component of a larger system. Information systems have close relationships and interdependencies with other sub-systems, making them inseparable from one another. An information system is just one component of various existing sub-systems, managed as property by a specific institution, organization, or company. Previous research or relevant studies aim to strengthen theories or phenomena related to the influence among variables. This article is structured using a qualitative method sourced from previous research literature by experts. The review's findings reveal components influencing Management Information Systems, namely: Software, Database, and Human Resources (Brainware). The results of this literature review indicate that 1) Software has an impact on Management Information Systems; 2) Databases also influence Management Information Systems; and 3) Human Resources also affect Management Information Systems.